Banking barriers to the green economy - Hans Degryse; Tarik Roukny; Joris Tielens (National Bank of Belgium, 2020)
In the race against climate change, financial intermediaries hold a key role in rapidly redirecting resources towards greener economic activities. However, this transition entails a dilemma for banks: entry of innovative and green firms in polluting industries risks devaluating legacy positions held with incumbent clients. As a result, banks exposed to such losses may be reluctant to finance innovation aiming to reduce polluting activities such as green house gas emissions. In this paper, we formalize potential banking barriers to investments in green firms that threaten the value of legacy contracts by affecting collateral pledged by incumbent clients to banks as well as probabilities of default. We show that themore homogeneous and concentrated the banking system is in a given industry, the fewer new innovative firms will be granted loanable funds. We further exploit data on credit allocations in Belgium between 2008 and 2018, to investigate the empirical relevancy of such barriers in polluting industries with larger exposures to green technology disruption. The results indicate that the market structure of the banking system may be key to facilitating a green economic transition highlighting the need for policies to address the role of brown legacy positions and heterogeneous bank business models.
Keywords: 330; Financial intermediation; innovation; barriers; climate change